1995
DOI: 10.1038/sj.bdj.4808663
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of lichen planus following removal of amalgam restorations in patients with proven allergy to mercury salts: a pilot study

Abstract: Thirteen patients with symptomatic oral lichen planus had been shown by patch testing to be allergic to ammoniated mercuric chloride. Replacement of amalgam restorations in these patients effected an improvement in all but one case. In some cases the resolution of symptoms was dramatic following the replacement of one or two fillings. The authors feel that the removal of all amalgam fillings need not be necessary except in the most intractable case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 0 publications
1
28
0
1
Order By: Relevance
“…These reactions are presumably due to allergic or toxic reactions to compounds released or generated, the Koebner phenomenon, or possibly due to plaque accumulated on the surfaces of the restorations (Holmstrup, 1991). Some of these oral lesions may improve after substitution of the amalgam by other materials (Finne et al, 1982;Jolly et al, 1986;Lind et al, 1986;Bolewska et al, 1990;Jameson et al, 1990;Skoglund and Egelrud, 1991;Laine et al, 1992;Bircher et al, 1993;Ostman et al, 1994;Henriksson et al, 1995;Smart et al, 1995;Bratel et al, 1996;Ibbotson et al, 1996), though this is often not the case with gingival lesions (Henriksson et al, 1995).…”
Section: (2) Drug-related White Lesions (A) Burns (See Above) (B) Licmentioning
confidence: 99%
“…These reactions are presumably due to allergic or toxic reactions to compounds released or generated, the Koebner phenomenon, or possibly due to plaque accumulated on the surfaces of the restorations (Holmstrup, 1991). Some of these oral lesions may improve after substitution of the amalgam by other materials (Finne et al, 1982;Jolly et al, 1986;Lind et al, 1986;Bolewska et al, 1990;Jameson et al, 1990;Skoglund and Egelrud, 1991;Laine et al, 1992;Bircher et al, 1993;Ostman et al, 1994;Henriksson et al, 1995;Smart et al, 1995;Bratel et al, 1996;Ibbotson et al, 1996), though this is often not the case with gingival lesions (Henriksson et al, 1995).…”
Section: (2) Drug-related White Lesions (A) Burns (See Above) (B) Licmentioning
confidence: 99%
“…These reactions are presumably due to allergic or toxic reactions to compounds released or generated, the Koebner phenomenon, or possibly plaque accumulated on the surfaces of the restorations (Holmstrup, 1991) Metal restorations Some lesions resembling OLP may occur in direct relation to amalgam restorations (Lundstrom, 1984;Lind et al, 1986;Bolewska et al, 1990a,b), and some of these oral lesions may improve after substitution of the amalgam by other materials (Finneetal., 1982;Jolly etal., 1986;Lind et al, 1986;Bolewska et al 1990a,b;Jameson et al, 1990;Skoglund and Egelrud, 1991;Laine et al, 1992;Bircher et al, 1993;Skoglund, 1994, Henriksson etal., 1995, Smartet al, 1995, Bratel et al, 1996Ibbotson et al, 1996), though this is often not the case with gingival lesions (Henriksson et al, 1995) Significant reactions to mercuric salts on skin-testing may be seen in some patients with OLP (Finne et al, 1982, Eversole andRinger, 1984;Mobacken et al, 1984a;lames et al, 1987;Ostman et al, 1994), though others have not found this (Hietanen et al, 1987) Finne et al (1982 demonstrated mercury sensitivity by patch testing in 62% of 29 patients with OLP and only 3.2% of a control group, and oral lesions regressed in a few patients when their amalgams were removed (Finne et al, 1982). Reactions to mercuric chloride have been reported (Skoglund and Egelrud, 1991;Smart et al, 1995). These…”
Section: Associations Of Olp With Systemic Diseasementioning
confidence: 99%
“…Intensive oral hygiene procedures may produce subjective and objective improvement of the lesions (Erpenstein, 1985;Holmstrup et al, 1990) and can also eliminate Candida from most lesions (Holmstrup et al, 1990). Attention should then be paid to the possibility of dental restorations inducing the lesions, since they may sometimes improve after replacement of amalgam with other restorative materials (Bolewska et at., 1990a,b;Skoglund and Egelrud, 1991;Smart et al, 1995;Ibbotson etal., 1996).…”
Section: Treatments In Oral Lichen Planusmentioning
confidence: 99%
“…19 It is good for dental use because it is strong, long lasting, well fitting, easy to handle, and cheap. Conventional silver amalgam fillings consist of about 50% mercury and about 50% alloy powder containing silver, tin, copper, and zinc.…”
Section: Commentmentioning
confidence: 99%